Analisis Kemampuan Literasi Matematika dalam Menyelesaikan Soal Aljabar Berbasis HOTS Ditinjau dari Kemampuan Awal Siswa - Florensia, Flofida; Oktaviana, Dwi; Firdaus, Muhamad (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze in depth the mathematical literacy abilities possessed by students at SMP Negeri 11 Sungai Ambawang which are reviewed based on the initial abilities possessed by students with three categories of initial abilities, namely high, medium and low levels. This research is a descriptive qualitative research method in the form of a case study. In this research, the case that will be studied is how mathematical literacy skills are in solving HOTS-based algebra problems. Data collection tools in this research are tests and interview instruments. The subjects of this research were 24 students in class VIII A of SMPN 11 Sungai Ambawang. In this research, it was concluded that students with a high level of initial ability were able to fulfill three indicators of mathematical literacy, namely understanding and formulating, using and applying, and interpreting, while students with a medium level of initial ability were only able to fulfill two indicators, namely understanding and formulating, using and apply but cannot interpret. Meanwhile, students with low initial abilities are unable to meet the three indicators.